Pengaruh pemberian informasi melalui Facebook terhadap peningkatan pengetahuan kehamilan remaja - Dimar Verminisnaini; Siti Tyastuti; Yuliasti Eka Purnamaningrum (Poltekkes Kemenkes Yogyakarta, 2013)
In Daerah Istimewa Yogyakarta there were 56,1% adolescent girls aged 16-20 who give birth 1-2 baby (BPS DIY Province 2011). While in Kulon Progo Regency from 2009-2011 there were increased percentage of adolescent pregnancy from 11,2%, 11,7% and 11,8%. The most adolescent pregnancy rate in Wates District. Giving appropriate information can improved knowledge of adolescent about adolescent pregnancy. Objective: to determine the effect of giving information by facebook toward knowledge improvement about adolescent pregnancy. Experimental study with pretest-posttest design with control group was brought. This study took place at 2 Wates High School as experimental group and 1 Wates High School as control group. Subject of this study was students grade X. this study composed of 53 students are respondent for each group. Instrumental of this study questionnaire. The result average pretest was 56,9% to experimental group dan the control groups was 67.7%. the result of average post-test was 91.0% to experimental group and the control group was 73.3%. the results of paired sample t test showed that experimental group while the control group was 5,7. The result of independent sample t-test showed that p-value 0.00 (p-value <0.05). conclusion: there are improved of giving information by facebook toward knowledge improvement about adolescent pregnancy of grade X at 2 Wates High School 2013.